A framework for systematic microplastic ecological risk assessment at a national scale. (15th June 2023) - Qiu, Yifei; Zhou, Shenglu; Zhang, Chuchu; Qin, Wendong; Lv, Chengxiang
Abstract: Microplastic pollution is widespread in terrestrial and aquatic environments; however, a systematic assessment of the ecological risks of microplastics is lacking. This study collected research studies on microplastics in soil, aquatic and sediment environments, and screened 128 articles including 3459 sites to assess the ecological risks posed by microplastics in China following a literature quality assessment. We developed a systematic ecological risk assessment framework for microplastics in terms of spatial characterization, biotoxicity and anthropogenic impacts. The results of the pollution load index indicated that 74% and 47% of the soil and aquatic environments studied, respectively, faced a medium or higher level of pollution. Comparing predicted no effect concentrations (PNEC) and measured environmental concentrations (MECs), revealed that soil (97.70%) and aquatic (50.77%) environmental studies were at serious ecological risk from microplastics. The results of the pressure-state-response model showed that the microplastic pollution in Pearl River Delta was in a high-risk state. In addition, we found that ultraviolet radiation and rainfall exacerbate soil microplastic pollution, and higher river runoff may carry large amounts of microplastic from the source. The framework developed in this study will help assess the ecological risks of microplastics in the region to promote the mitigation of plastic pollution. Graphical abstract: Image 1 Highlights: A systematic ecological risk assessment framework for microplastics was developed. This framework includes spatial representation, biotoxicity and anthropogenic impact. MP pollution of different land use types was significantly different. Soil and aquatic environments were at serious ecological risk from microplastics.